Features of laser welding of wood-cutting band saws - Rebeznyuk, I.T.; Lazarchuk, K. (Forestry, Forest, Paper and Woodworking Industry, 2019)
Abstract. Laser welding is the most effective method of joining the ends of band saws according to the high level of existing jointing requirements; using this method allows you to form anesthetic, even and smooth sound weld without deformation. Laser welding has a number of advantages but at the same time the main disadvantage of laser welding is the high cost of equipment and the need for highly qualified maintenance. The paper considers the main features of the method for joining a number of band saws into an endless band saw by laser welding. The specific feature of laser welding is that it produces the highest degree of energy density on a tiny spot. The essence of the laser welding process sis that inartificially generated laser beam is used as a source of thermal energy to per form the work. High cooling rates of the weld (up to 3,000° C/s) and high speeds of welding (up to 120 m/h) of low-carbon steels affect the ir primary and secondary structure. The same factors provide a disordered fine-grained structure, which contributes to an increased resistance of the weld to the appearance of hot cracks. The laser welding of metals operates in three modes, the advantages and disadvantages of these modes being analyzed. Annealing after welding, accompanied by heating to a temperature of 450–470° C and holding for 30 s (recommended by Rentgen – the CR400 steel manufacturer) causes a gradual equalization of the hardness distribution. In the CR400 steel, containing chromium and tungsten at the lower allowable limit (3,5% and 5,3%, respectively), complete recovery of hard ness after annealing is not observed. Fluctuation sin hardness reach 30–35%, which negatively affects the strength of the saw. To eliminate this shortcoming, it is necessary to equalize the hardness, which can be provided by a special thermal strengthening. It is proposed to develop modes of laser thermal strengthening of the weld after the welding process, which will significantly increase the strength of the tool.